2010
DOI: 10.1016/j.jtbi.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation and the evolution of species’ ranges under climate change

Abstract: The potential impact of climate change on biodiversity is well documented. A well 6 developed range of statistical methods currently exists that projects the possible future habitat of a species directly from the current climate and a species distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
202
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(208 citation statements)
references
References 49 publications
6
202
0
Order By: Relevance
“…Conversely, in species with very limited dispersal, locally adapted populations may simply go extinct if they lack the capacity to evolve in response to new conditions (Atkins and Travis, 2010;Sanford and Kelly, 2011;Kelly et al, 2012). Several studies have found putatively adaptive differences in thermal physiology between populations of species with limited dispersal (Grosholz, 2001;Kuo and Sanford, 2009;Sorte et al, 2011) and even in certain widely dispersing species, e.g.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Conversely, in species with very limited dispersal, locally adapted populations may simply go extinct if they lack the capacity to evolve in response to new conditions (Atkins and Travis, 2010;Sanford and Kelly, 2011;Kelly et al, 2012). Several studies have found putatively adaptive differences in thermal physiology between populations of species with limited dispersal (Grosholz, 2001;Kuo and Sanford, 2009;Sorte et al, 2011) and even in certain widely dispersing species, e.g.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…As the suitable climate space for a species shifts poleward (3), populations previously well adapted to the historical climate in a particular region may experience strong selection to adapt to rapidly warming local temperatures (4)(5)(6)(7)(8)(9)(10). Rapid evolutionary response to climate change has already been observed (11,12), but it remains unclear whether evolutionary response can keep pace with rapidly changing local adaptive optima (6,8,(13)(14)(15).…”
mentioning
confidence: 99%
“…Climatic changes have already occurred (Jones et al, 1999;Meehl et al, 2007), and in biological systems there is mounting evidence that these relatively minor changes have already resulted in altered phenology, range shifts, and population declines (e.g., Parmesan, 2006;Freeman and Freeman, 2014). Much greater climate change lies in our immediate future (Meehl et al, 2007), and the impacts of this impending change are likely to be manifold and complex (e.g., Atkins and Travis, 2010;Norberg et al, 2012). Despite inherent uncertainties in how, exactly, climate change will play out, and how this will impact biodiversity (Moritz and Agudo, 2013), there are certainly grounds for deep concern regarding the future of many species (Thomas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%